Electrospun PA6 Nanofibers Bearing the CeO2 Dephosphorylation Catalyst - Henych, Jiří; Ryšánek, Petr; Št'astný, Martin; Němečková, Zuzana; Adamec, Slavomír; Kormunda, Martin; Kamínková, Simona; Hamalová, Kateřina; Tolasz, Jakub; Janoš, Pavel (ACS omega, 2023)
Two types of CeO2 nanoparticles (CeNPs) prepared by low-temperature (<100 °C) precipitation methods in water were successfully immobilized in a matrix of electrospun PA6 nanofibers. The colloidal solutions of CeNPs in AcOH were directly mixed with the polymer solution before the needle electrospinning process, thereby achieving their good dispersion in the nanofibers. CeNPs embedded in the structure and on the surface of nanofibers exposing their reactive surfaces showed robust dephosphorylation catalytic activity, as demonstrated by monitoring the hydrolytic cleavage of three phosphodiester molecules (p-NP-TMP, p-NPPC, BNPP) in water by the HPLC method. This procedure allowed us to study the kinetics and mechanism of the hydrolytic cleavage and the ability of immobilized CeNPs to cleave different types of P-O bonds. One of the main hydrolysis products, p-nitrophenol, was effectively adsorbed on PA6 nanofibers, which may allow the selective separation of the degradation products after hydrolysis.